Pengaruh Intensitas, Motif, dan Kredibilitas Komunikator terhadap Kepuasan Menonton Youtube "Nihongo Mantappu" - Muthia Alya Rahmawati; Novita Haryono (Jurnal Komunikasi Massa, 2025)
In 2023, YouTube, with 2.52 billion users, became a popular video platform, with travel vlogs such as Wasedaboys Japan Trip from Jerome Polin on the "Nihongo Mantappu" channel, which reached 10.5 million subscribers. These videos received positive comments regarding its content, as well as various viewer motives for watching, such as stress relief or seeking new information, as shown in the We Are Social Indonesia (2024) study, which highlights different viewer motives in consuming YouTube content. This study aims to analyze the effect of viewing intensity, viewing motives, and communicator credibility on viewer satisfaction using the Uses and Gratification Theory. This research uses a quantitative method with data collection through surveys. The sample consisted of 100 respondents who are subscribers of the "Nihongo Mantappu" channel, selected using nonprobability sampling techniques. The data obtained was analyzed using SPSS. The results showed that viewing intensity (X1) had no significant effect on viewing satisfaction (Y) as the significance level was 0.492 > 0.05, while viewing motives (X2) and communicator credibility (X3) had a significant effect on viewing satisfaction with a significance level of 0.000 < 0.05. The largest influence was found in the viewing motives variable, with an influence value of 65.4%. Simultaneously, all independent variables (X1, X2, X3) had an effect on viewing satisfaction (Y) of 87.2%, while 12.8% was influenced by other factors not identified in this study.